Biodiversity and techno-functional properties of lactic acid bacteria in fermented hull-less barley sourdough - Cakir, Elif; Arici, Muhammet; Durak, Muhammed Zeki (SOC BIOSCIENCE BIOENGINEERING JAPAN, 2020)
The aim of this study was to characterize the biodiversity of lactic acid bacteria (LAB) isolated from spontaneously-fermented hull-less barley sourdough and to determine its technological properties. Biodiversity was investigated by analysis of colonies isolated from sourdough on four different agar media. Of the 80 isolates, 67 were rapidly pre-identified as LAB using Fourier transforms infrared spectroscopy (FTIR). As a result of cluster analysis, 32 lactic acid bacteria chosen from different branches were identified. According to the polymerase chain reaction (PCR) results, 9 different species were identified: Pediococcus (dominant species), Lactobacillus curvatus, Lactobacillus brevis, Lactobacillus plantarum, Lactobacillus fermentum, Lactobacillus musae, Lactobacillus paralimentarius, Leuconostoc mesenteroides and Lactobacillus equigenerosi. The most species and strain diversity among the media was determined in ModMRS environment. Unlike other studies about hull-less barley, Lactobacillus equigenerosi was identified in this study. LABs were identified with salt and acid tolerance. Generally, different levels of antibacterial activity in these species were shown against (rope spoilage) food borne pathogens. The greatest antimicrobial effect was observed for Pediococcus acidilactici SAB26, Lactobacillus plantarum SAB15 and Pediococcus acidilactici SAB13 compared to the other strains. Pediococcus species were found to have the highest antifungal effect against Penicillium carneum, Aspergillus flavus and A. niger. The phytase activity of LAB, which increases mineral bioavailability, was observed to be highest in Lactobacillus plantarum, Pediococcus pentosaceus, and Leuconostoc mesenteroides. (C) 2020, The Society for Biotechnology, Japan. All rights reserved.
Keywords: Hull-less barley sourdough; Lactic acid bacteria; Polymerase chain reaction; Antimicrobial activity; Phytase activity; YEAST MICROBIOTAS; DIETARY FIBER; IDENTIFICATION; STRAINS; SPECTROSCOPY; QUALITY; PHYTASE; BAKING; Biotechnology & Applied Microbiology; Food Science & Technology